Investigations sur une crise de mortalité à Boulogne-sur-Mer (Pas-de-Calais, XVIIIe s.). Hypothèses d’interprétation - Dominique Castex; Hélène Réveillas (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Seven simultaneous burials, representing a total of 39 individuals and dated as early as the 18th century, were found at the excavation site of l’Ilot Saint-Louis at Boulogne-sur-Mer (Pas-de-Calais). The simultaneity of the bone deposits, the contemporaneity of the different burial structures and the recurrence of the phenomenon lead us to believe that the site is the result of an abrupt peak in mortality. Historical, archaeological and anthropological arguments rule out the hypotheses of war or famine as the cause of this peak, leaving that of an epidemic. Sex distribution is well-balanced and the number of adult and immature individuals is almost identical. However certain peculiarities in the ratio between the different groups of immature individuals and that of a demography considered “natural” become apparent. These peculiarities, when studied historically, medically and demographically, permit us to eliminate certain epidemics from consideration. The most likely proposition would seem to be smallpox, although other poorly documented illnesses, known to be recurrent at that time, cannot be totally excluded. A more precise explanation of the epidemic responsible for the deaths at Boulogne will need further research, particularly a more thorough study of historical records, but also by molecular palaeobiochemical analysis, in order to identify speciﬁc pathogens.